Концептуальні засади організації мотивації працівників у сфері зовнішньоекономічної діяльності відповідно до умов соціально відповідального ведення бізнесу - Кальченко, Сергій Володимирович; Кальченко, Сергей Владимирович; Kalchenko, Serhii (Мелітополь: Люкс, 2015)
UK: Стаття присвячена дослідженню особливостей організації менеджменту зовнішньоекономічної діяльності. Автор проаналізував наукові підходи до організації мотиваційного механізму в системі менеджменту зовнішньоекономічної діяльності. Особливу увагу приділено шляхам адаптації мотиваційної системи зовнішньоекономічної діяльності до принципів соціально відповідального бізнесу. Автор обґрунтував необхідність оптимізації теоретичних підходів щодо оптимізації мотиваційної системи менеджменту зовнішньоекономічної діяльності. Автор розглянув можливість участі підприємства в міжнародних соціально-економічних проектах як один з аспектів соціально-відповідального ведення бізнесу. EN: The article investigates the characteristics of the organization of foreign economic activity management. The author has analyzed the scientific approaches to the organization of the motivational mechanism in the system of foreign economic activity management. Particular attention is paid to ways of adapting motivational system of foreign economic activity to the principles of socially responsible business. Author substantiated the need to optimize the theoretical approaches regarding the optimization of the motivational system of management of foreign economic activity. The article points to the importance of ensuring the effective participation of management in the enterprise management. The author has considered the motivational system of management of foreign economic activity on the principles of socially responsible business. The article points to the multi-level nature of the organization of socially responsible business. Specificity of the multilevel nature of the socially responsible business involves the need for a set of measures on the part of the company's management. These activities include not only purely economic, but also social steps. In this regard, important is the willingness of management to integrate the company in regional socioeconomic projects. It is necessary to take into account the current trends of globalization of national economic space. The author has considered the possibility of the company's participation in international socio-economic projects as one of the aspects of socially responsible business.
Keywords: менеджмент зовнішньоекономічної діяльності; мотивація; соціально відповідальний бізнес; international management; motivation; socially responsible business